2014
DOI: 10.1080/00380768.2014.926781
|View full text |Cite
|
Sign up to set email alerts
|

Vertical migration of radiocesium and clay mineral composition in five forest soils contaminated by the Fukushima nuclear accident

Abstract: In forest soils contaminated by radiocesium ( 134 Cs and 137 Cs), deposition from the Fukushima nuclear accident, clay minerals might play important roles in long-term cesium (Cs) dynamics through sorption. To determine whether radiocesium can be retained within the organic layer and the upper mineral soil layers in the Fukushima region, we investigated the vertical distribution of 134 Cs and 137 Cs and the clay mineral composition in five soil profiles of varying radiocesium deposition levels and vegetation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 48 publications
4
51
0
Order By: Relevance
“…Takahashi et al (2015) found that the proportion of radiocesium in leaf litter, relative to soil, decreased from~90% in 2011 to 18e14% in 2012. Fujii et al (2014) also noted a significant decrease in the percentage of radiocesium in the leaf litter, decreasing from between 44e65% in 2011 to 14e27% in 2012. The transfer of radiocesium from litter to soil is controlled by rainfall and litter decomposition.…”
Section: Forest Depositionmentioning
confidence: 89%
See 1 more Smart Citation
“…Takahashi et al (2015) found that the proportion of radiocesium in leaf litter, relative to soil, decreased from~90% in 2011 to 18e14% in 2012. Fujii et al (2014) also noted a significant decrease in the percentage of radiocesium in the leaf litter, decreasing from between 44e65% in 2011 to 14e27% in 2012. The transfer of radiocesium from litter to soil is controlled by rainfall and litter decomposition.…”
Section: Forest Depositionmentioning
confidence: 89%
“…The rainfall that occurred immediately after the accident fallout may have been a factor in the radiocesium depth migration in forest soils (Teramage et al, 2014b) along with rainfall volume in general (Fujii et al, 2014). Further, rainfall was listed as a potential factor for the depth migration in the beach sand samples (Satou et al, 2015).…”
Section: Figmentioning
confidence: 99%
“…A smaller amount of particulate matter transported from the experimental plot indicates a shallower erosion depth in the plot. Base on the 137 Cs depth distribution and its temporal changes in the forest soil after the FDNPP accident (Fujii et al, 2014;Takahashi et al, 2015), the shallower erosion depth increased the 137 Cs activity of eroded soil particles, even two to three years after the accident. However, it is extremely difficult to explain the differences in the 137 Cs activities of the particulate matter based on the differences in particulate matter weight (Table 8), which were less than 1 mm when the weight was converted into the erosion depth, assuming a dry soil density of 1.0 g cm À3 .…”
Section: Output Via the Surface Runoff Processmentioning
confidence: 99%
“…The raw organic layer holds 52 % of the Fukushima-derived 137 Cs and 25 % of the pre-Fukushima 137 Cs at the time of the soil sampling. Fujii et al (2014) also investigated the role of the organic layer of soil collected in Fukushima Prefecture (Kawauchi, Ohtama, and Tadami Town) during AugustSeptember of 2011 and 2012. The vertical soil distribution of 134 Cs and 137 Cs suggested that most cesium was retained in the organic layer and upper mineral soil layer under different levels of deposition.…”
Section: Cs and 137 Cs Before And After The Fukushima Nuclear Accidentmentioning
confidence: 99%